The evangelistic note - Dawson, William James (Fleming H. Revell company, 1905)
The evangelistic note.--The social significance of Christian love.--Our duty to the bystander.--The unavoidable Christ.--The courage to forget.--The ministry of night.--God waiting man's answer.--The last step.--To the uttermost.--Sons of the tabernacle.--The seasons of the soul.--Self-reservation.--Saving faith.--Christ among the common things of life.